From the point of view of the VEWs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
More about attending courses, this time from Peter Ifeanyi Duru, of Orlu, Nigeria who asks: 'Can t CTA organise or extend its seminars to village extension workers (VEWs) and, considering their financial status, extend its benevolence to sponsoring...